100 Years of Women's Suffrage : A University of Illinois Press Anthology - Durante, Dawn (Book collections on Project MUSE., 2019)
"Over the last several decades, many University of Illinois Press publications have illuminated the key figures and diverse types of work across gender, race, and class that contributed to the suffrage movement and women voting. This anthology contains some of the most influential previously published chapters from UIP monographs and edited volumes on women's suffrage and contemporary voting issues. The year 2020 boasts the 100th anniversary of women's right to vote, and this volume is intended to commemorate the centennial of the nineteenth amendment"--